2021
DOI: 10.1371/journal.pone.0260960
|View full text |Cite
|
Sign up to set email alerts
|

Exploration of physiological and biochemical processes of canola with exogenously applied fertilizers and plant growth regulators under drought stress

Abstract: Environmental stresses may alter the nutritional profile and economic value of crops. Chemical fertilizers and phytohormones are major sources which can enhance the canola production under stressful conditions. Physio-biochemical responses of canola altered remarkably with the use of nitrogen/phosphorus/potassium (N/P/K) fertilizers and plant growth regulators (PGRs) under drought stress. The major aim of current study was to evaluate nutritional quality and physio-biochemical modulation in canola (Brassica na… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
6
0
2

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 51 publications
1
6
0
2
Order By: Relevance
“…On the other hand, under drought stress conditions the relative water content decreased when compared to normal irrigation as a control treatment (T1). A similar result was presented by Aslam et al (2021), who found a reduction in leaf water content when using chemical fertilizer alone under severe evaporation for improved Canola growth, decreasing relative water content as a result of water limitation. In contrast, the application of microbial biofertilizer (PGPR) maintained relative water content in plant leaves.…”
Section: Discussionsupporting
confidence: 83%
“…On the other hand, under drought stress conditions the relative water content decreased when compared to normal irrigation as a control treatment (T1). A similar result was presented by Aslam et al (2021), who found a reduction in leaf water content when using chemical fertilizer alone under severe evaporation for improved Canola growth, decreasing relative water content as a result of water limitation. In contrast, the application of microbial biofertilizer (PGPR) maintained relative water content in plant leaves.…”
Section: Discussionsupporting
confidence: 83%
“…There is no doubt that one of the most important changes in metabolic functions during drought is the loss of photosynthetic pigments or a decrease in their synthesis. Numerous studies have reported that drought-induced oxidative stress significantly reduces chlorophyll content in crop plants [ 28 , 34 , 35 , 40 ]. This was also confirmed by the data of our study, which showed that moderate and severe drought stress significantly reduced the content of chlorophyll a, b compared to control plants ( Table 4 ).…”
Section: Discussionmentioning
confidence: 99%
“…Similar drought-induced oxidative stress was recorded in oilseed rape plants in studies by other authors [ 28 , 34 , 36 ]. Excessive concentrations of free radicals, including H 2 O 2 , can cause damage to cell membranes, ion leakage, and osmotic imbalance, so maintaining their level is very important [ 34 , 40 ]. Plant spraying with exogenous proline significantly reduced H 2 O 2 content in prolonged-drought-stressed rapeseed leaf tissues.…”
Section: Discussionmentioning
confidence: 99%
“…Adequate soil fertility can lead to better plant growth and yield and higher oil content [75,76]. Adequate soil fertility can lead to better plant growth and yield and higher oil content [77,78]. However, excessive use of fertilizers can lead to the accumulation of nitrates in B. napus seeds, which can be harmful to human health [79].…”
Section: Environmental Factorsmentioning
confidence: 99%